PENGARUH MEDIA PAPAN PINTAR BANGUN DATAR TERHADAP HASIL BELAJAR SISWA KELAS II SD NEGERI 185 PALEMBANG - Atikah, Aryanti; Wardiah, Dessy; Tanzimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine whether there is an effect of the use of flat shape smart board media on the learning outcomes of second-grade students of SD Negeri 185 Palembang. The method used in this study is Quasi Experiment with a quantitative approach. The research design used is Non-Equivalent Control Group Design. The data collection technique in this study is a test. The sample in this study were students of class II C and class II D, totaling 56 students. The data obtained were then analyzed using normality tests, homogeneity tests, and hypothesis tests using independent samples t-tests. The results of this study indicate that there is an effect of the use of flat shape smart board media on student learning outcomes. This is evidenced by the results of the t-test which shows a significance value (Sig. 2-tailed) of 0.000 <0.025, so Ha is accepted and Ho is rejected, which means that the flat shape smart board media has a significant effect on the mathematics learning outcomes of second-grade students of SD Negeri 185 Palembang.